2018
DOI: 10.1111/1462-2920.14044
|View full text |Cite
|
Sign up to set email alerts
|

The mycobiota of the sand fly Phlebotomus perniciosus: Involvement of yeast symbionts in uric acid metabolism

Abstract: The knowledge of the fungal mycobiota of arthropods, including the vectors of human and animal diseases, is still limited. Here, the mycobiota associated with the sand fly Phlebotomus perniciosus, the main vector of leishmaniasis in the western Mediterranean area, by a culture-dependent approach (microbiological analyses and sequencing of the 26S rRNA gene), internal transcribed spacer (ITS) rRNA amplicon-based next-generation sequencing, fluorescence in situ hybridisation (FISH), and genome sequencing of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 70 publications
(78 reference statements)
0
10
0
Order By: Relevance
“…Under this perspective, the hydrolytic profiles of our collection revealed that 16.1% of the isolates, mainly belonging to Ochrobactrum, Providencia, Pseudomonas, and Stenotrophomonas genera, showed the ability to degrade uric acid, the main nitrogenous waste compound excreted by Malpighian tubules into the insect anterior hindgut ( Supplementary Table S1; Engel and Moran, 2013). Degradation of urea (which could derive, in turn, from uric acid utilization, Martin et al, 2018) with ammonia production was carried out by 32.6% of the strains of our collection, while the majority of the isolates (90.7%) were able to release ammonia from peptone. Protease activity, and specifically the one exerted by serine proteases, was mainly retrieved in the posterior part of the midgut, which reached a pH value of 8.3 (Bonelli et al, 2019).…”
Section: Discussionmentioning
confidence: 95%
“…Under this perspective, the hydrolytic profiles of our collection revealed that 16.1% of the isolates, mainly belonging to Ochrobactrum, Providencia, Pseudomonas, and Stenotrophomonas genera, showed the ability to degrade uric acid, the main nitrogenous waste compound excreted by Malpighian tubules into the insect anterior hindgut ( Supplementary Table S1; Engel and Moran, 2013). Degradation of urea (which could derive, in turn, from uric acid utilization, Martin et al, 2018) with ammonia production was carried out by 32.6% of the strains of our collection, while the majority of the isolates (90.7%) were able to release ammonia from peptone. Protease activity, and specifically the one exerted by serine proteases, was mainly retrieved in the posterior part of the midgut, which reached a pH value of 8.3 (Bonelli et al, 2019).…”
Section: Discussionmentioning
confidence: 95%
“…The identification of these fungi in Aedes spp., which complete their life cycle in anthropized environments, suggests these mosquitoes could contribute to the dissemination of pathogenic yeasts, thus increasing their public health relevance (Bozic et al, 2017). Meyerozyma guilliermondii colonizes the guts of insects from several taxa (Stefanini, 2018); for instance, it is the dominant species in the mycobiota of the leishmaniasis vector Phlebotomus perniciosus where it was proposed to contribute in uric acid degradation (Martin et al, 2018). Metabolic interactions between members of the mycobiota and the mosquito host are being discovered.…”
Section: Beyond Bacteriamentioning
confidence: 99%
“…In the sand fly Phlebotomus perniciosus, the main vector of leishmaniasis in the western Mediterranean area, it was recently showed that the yeast Meyerozyma guilliermondii colonizes the midgut of adults and larvae as well as the distal part of the Malpighian tubules of females. Moreover, M. guilliermondii possesses an uricolytic activity and presents in its genome the complete uric acid degradation pathway suggesting that this yeast might contribute to the removal of the excess of uric acid after the blood meal of the insect host [54]. Interestingly, M. guilliermondii has been also detected in several mosquito species [29,32] and might also be involved in the degradation of the uric acid accumulated in the Malpighian tubules after the blood meal.…”
Section: Mutualistic Interactions and Their Role In Digestive Processesmentioning
confidence: 99%